27. WHO PREQUALIFICATION FOR MEASLES VACCINE MVVAC PRODUCED BY POLYVAC: CHALLENGES AND LESSONS LEARNED (Vietnam Journal of Community Medicine, 2024)
Prequalification (PQ) is the WHO’s comprehensive assessment of the quality, safety and effectiveness of vaccines to be purchased by UNICEF or other organizations of the United Nations. In Vietnam, there are 4 manufacturers producing vaccines, providing for the National Expanded Immunization Program to ensure domestic vaccine supply chain. Currently, Center for Research and Production of Vaccines and Biologicals (POLYVAC) is the first manufacturer to submit an application to WHO-PQ from May 31, 2021 for MVVAC Measles vaccine. This report aimed to provide useful information about the detailed process and legal requirements for applying to WHOPQ for vaccines. The article also mentioned common difficulties in the process of applying for PQ for products manufactured in Vietnam due to differences in procedures and requirements of WHO and Vietnam as well as responding to updates in WHO regulations. In addition, we also shared some of POLYVAC’s practical challenges and solutions to achieve initial successes. Therefore, other vaccine manufacturers in Vietnam can refer to the information and have lessons learned to prepare for WHOPQ applications in the future.
Keywords: Measles vaccine, MVVAC, POLYVAC, Prequalification.